Meningkatkan Loyalitas Konsumen Scarlett Whitening Melalui Brand Experience, Kepuasan, dan Brand Attachment di Yogyakarta - Hayon, Laurensia Barekina; Setiawan, Budi; Lukitaningsih, Ambar (Jambura Economic Education Journal, 2025)
The purpose of this study is to examine how customer loyalty to Scarlett Whitening is enhanced through brand experience, brand satisfaction, and brand attachment in Yogyakarta. The methodology employed in this research is quantitative. Data were collected using a questionnaire, and the data analysis was conducted using SmartPLS version 3. The sample size for this study consisted of 204 Scarlett Whitening users in Yogyakarta. The findings indicate that although brand experience does not have a positive impact on brand loyalty, it does positively influence brand satisfaction. However, brand satisfaction does not have a positive impact on brand loyalty. Brand experience has a positive impact on brand attachment, and brand attachment positively influences brand loyalty. Moreover, brand satisfaction fails to provide positive feedback on both brand loyalty and brand experience, whereas brand attachment successfully provides positive feedback on brand loyalty.